On‐Chip Plasmonic Vortex Interferometers - Lang, Yuanhao; Xu, Quan; Chen, Xieyu; Han, Jie; Jiang, Xiaohan; Xu, Yuehong; Kang, Ming; Zhang, Xueqian; Alù, Andrea; Han, Jiaguang; Zhang, Weili (Laser & photonics reviews, 2022)
Since the late 19th century, enormous endeavors have been made in extending the scope and capability of optical interferometers. Recently, plasmonic vortices that strongly confine the orbital angular momentum to surface have attracted considerable attention. However, current research interests in this area have focused on the mechanisms and dynamics of polarization‐dependent single plasmonic vortex generation and evolution, while the interference between different plasmonic vortices for practical applications has been unexplored. Here, a method for flexible on‐chip spin‐to‐orbital angular momentum conversion is introduced, resulting in exotic interferograms. Based on this method, a new form of interferometers that is realized by the interference between customized plasmonic vortices is demonstrated. Within wavelength‐scale dimension, the proposed plasmonic vortex interferometers exhibit superior performance to directly measure the polarization state, spin and orbital angular momentum of incident beams. The proposed interferometry is straightforward and robust, and can be expected to be applied to different scenarios, fueling fundamental advances and applications alike. A new form of optical interferometers is realized by customizing the plasmonic vortex generation from two spin channels. Based on the interference among different plasmonic vortices, the light beam information including polarization state, spin and orbital angular momentum can be broken down at spin‐basis and captured in an ultra‐compact interferogram, exhibiting versatility and superior performance.